Fragment-specific fixation of trimalleolar fractures utilizing the posterolateral approach: A preliminary experience. (10th May 2019) - Gupta, Sandeep; Virk, Jagandeep Singh; Malhotra, Anubhav; Garg, Sudhir Kumar
Introduction: Ankle fractures involving posterior malleolus are disabling injuries if not managed properly. Clinical and functional outcome of ankle fractures involving posterior tibial plafond is significantly worse. Although the surgical approach and techniques to reduce and fix this fracture are well described in the literature, there still seems to be divided consensus among orthopedic surgeons regarding the same. Methods: In this case series of eight patients with trimalleolar fractures, a posterolateral approach was used for fixation of posterior malleolus in all the cases. A preoperative computed tomography scan formed an integral part of management of such injuries. The Olerud and Molendar scoring system was employed at 12 months of follow-up to assess the functional outcome. Weight-bearing X-rays were taken to assess for any ankle arthritis. Results: The average age of patients was 48.8 years. The most common mode of sustaining injury was twisting of the ankle joint ( n = 5). The average time to union and full weight-bearing was 12.8 weeks (range 10–16 weeks). An excellent functional outcome in four patients and a good outcome in the rest of the four patients were obtained at the end of 12 months of follow-up. No significant ankle arthritis or complications were encountered. Conclusion: Appropriate preoperative imaging evaluation is an integral part of planning for these complex injuries. The posterolateral approach provides good exposure for appropriate visualization. Stable fixation of posterior malleolus in trimalleolar fractures plays a vital role in obtaining a positive clinical and functional outcome.